Rural women of Iran - Women's Solidarity Association of Iran (Tehran : Ministry of Culture and Islamic Guidance, 1995)
Rural women and bases for social growth--The role of rural women--Providing service to rural women.
Keywords: MUJERES RURALES; IRAN (REPUBLICA ISLAMICA)